Peri‐ictal hypoxemia during temporal lobe seizures: A SEEG study. Issue 15 (15th June 2022) - Jung, Julien; Bouet, Romain; Catenoix, Hélène; Montavont, Alexandra; Isnard, Jean; Boulogne, Sébastien; Guénot, Marc; Ryvlin, Philippe; Rheims, Sylvain
Abstract: Focal seizures originating from the temporal lobe are commonly associated with peri‐ictal hypoxemia (PIH). During the course of temporal lobe seizures, epileptic discharges often not only spread within various parts of the temporal lobe but also possibly insula and frontal lobe. The link between spatial propagation of the seizure discharges and PIH is still unclear. The present study investigates the involvement of several brain structures including medial temporal structures, temporal pole, anterior insula, and frontal cortex in the occurrence of PIH. Using quantitative indices obtained during SEEG ( stereoencephalography) recordings in 38 patients, we evaluated the epileptogenicity, the spatial propagation, and functional connectivity between those structures during seizures leading to PIH. Multivariate statistical analyses of SEEG quantitative indices showed that temporal lobe seizures leading to PIH are characterized by a strong involvement of amygdala and anterior insula during seizure propagation and a more widespread involvement of medial temporal lobe structures, lateral temporal lobe, temporal pole, and anterior cingulate at the end of the seizures. On the contrary, seizure‐onset zone was not associated with PIH occurrence. During seizure propagation, anterior insula, temporal pole, and temporal lateral neocortex activities were correlated with intensity of PIH. Lastly, PIH occurrence was also related to a widespread increase of synchrony between those structures. Those results suggest that PIH occurrence during temporal lobe seizures may be related to the activation of a widespread network of cortical structures, among which amygdala and anterior insula are key nodes. Abstract : Focal seizures originating from the temporal lobe are commonly associated with peri‐ictal hypoxemia (PIH). Peri‐ictal hypoxemia is associated with a strong involvement of amygdala and anterior insula during seizure propagation and a more widespread involvement of medial and lateral temporal lobe, temporal pole and frontal lobe at the end of the seizures.